[PP.05.34] METABOLIC SYNDROME-RELATED FEATURES IN CONTROLLED AND RESISTANT HYPERTENSIVE SUBJECTS. (September 2017) - Catharina, A. Santa; Modolo, R.; Ritter, A.; Sabbatini, A.; Correa, N.; Brunelli, V.; Fraccaro, N.; Almeida, A.; Lopes, H.; Moreno, H.; De Faria, A.
Abstract : Objective: The purpose of this study was to evaluate the prevalence of metabolic syndrome (MetS) and the clinical features associated with it in resistant and mild to moderate hypertensives. Design and method: This cross-sectional study included 236 patients, (i) 129 mild to moderate hypertensive patients and (ii) 107 patients with resistant hypertension (RHTN). We determined blood pressure measurements, bioimpedance parameters and adipokines levels. Target organ damages such as microalbuminuria (MA), cardiac hypertrophy and arterial stiffness were also assessed. Results: We found a prevalence of 73% in resistant and 60% in mild-to-moderate hypertensive patients. The patients with MetS showed a higher prevalence of MA equal or higher than 30 mg/g compared to their counterparts (20% vs. 4%). Adiponectin levels were significantly lower in patients with MetS (5.30 vs. 7.50 μg/mL), while leptin demonstrated to be increased in those patients, compared to the subjects without MetS (21.0 vs. 15.7 ng/mL). Finally, in a multiple regression analysis MA (OR = 8.51; p = 0.01), leptin/adiponectin ratio (LAR) (OR = 4.13; p = 0.01) and RHTN (OR = 3.75; p = 0.03) were independently associated with the presence of MetS, apart from potential confounders. Conclusions: Our findings suggest that the metabolic derangements present in MetS tend to develop early signs of end-organ damage with hormonal changes in hypertensive patients. Indeed, LAR may be useful as a reliable biomarker for identifying those who are at risk for developing MetS.